Aprender para ensinar, ensinar para aprender: um estudo do processo de aprendizagem profissional da docência de alunos-já-professores. - Lima, Soraiha Miranda de (2003)
This essay is included in the ambit of the searches that intend to make a profound study of the teacher s professional learning process. The studies made in the ambit of this perspective have evidenced that teacher s professional learning occurs along the life. It has a fundamental space of the continuous improvement in the quotidian action. This is delineated by the teacher s personal and professional biography. Nevertheless there is scarce information about the influences of the formation courses on the teacher s professional learning process and this is the purpose of this study oriented by the search question: What is the influence of the Pedagogy Course in the teacher s professional learning process of the pupils-already-teachers? To execute this work I selected six pupils-already-teachers of the 4th year of Pedagogy of the Campus of Rondonópolis, of the Universidade Federal de Mato Grosso and who are working in the initial classes of the fundamental education of the public system. This essay has as reference the qualitative approaches of the research and it uses the individual interview with profundity as main proceeding for the investigation. The information achieved with this study reveal that the school represented, in the pupils-already-teachers lives, an important perspective of social rising and the mastership was a more possible alternative of the study, maybe the only for them in the last of the fundamental education. The search also reveals that the entrance in the teaching profession was, to some extent, accidental . By the material circumstances they became teachers - although they wouldn t want to be one and they became steadies in the profession. So the teaching profession was not a deliberated and conscious professional choice. Moreover the information achieved with this search allow to localize places, institutions, people, contexts that contributed for the teacher s learning: experience with the student, practice in the classroom, dialogue whit the colleagues, dynamic of the school, courses, institutional assistance of bureau of the education, Pedagogy course. It was indicated as fundamental in the teacher s professional learning process because it helps them to understand the society and the work that happens in the inner of the classroom. The research reveals the teacher s professional learning is a complex and multidimensional process marked by the quotidian action and personals value. It also reveals that the information, experiences, practices, knowledge, theories divulged by the Pedagogy Course represented a fundamental opportunity of the learning of the pupils-already-teachers when they were articulated with their quotidian experiences in the classroom. So this study indicates that the teachers education transcends the course but it cannot do without him.